Morphological identification of plant parasitic nematodes associated with Rambutan (Nephelium lappaceum Linn.) - Kiunisala, P. B.; Panalangin, Jr. D. D.; Locsin, S. A.; Alvarez, L. V.; Rendon, A. O.; Mapanao, C. P.; Zurbano, L. Y.; Bellere, A. D. (International Journal of Agricultural Technology, 2021)
Plant-parasitic nematodes are one of the significant crop problems affecting various crop productions worldwide. Rambutan (Nephelium lappaceum) is one of the most economically important crops in the Philippines which its association with plant parasites is not well known. This paper aims to identify the species of plant-parasitic nematodes associated with rambutan as well as the manifestation of these plant parasites related to this fruit tree. The nematodes from soil and roots samples were extracted using the Baermann tray method and were identified under the light microscope based on their morphological characters. Four species of plant-parasitic nematodes were identified, namely: Discocriconemella spp., Hemicycliophora spp., Helicotylenchus spp. and Heterodera/Globodera spp. Where in Discocriconemella spp. was the most frequently occurring species in the soil with a total of 40%. The prevalence of Discocriconemella spp. indicates that the soil environment in the study area is favorable for these organisms but also suggest that abiotic factors such as Physico-chemical properties do have a relationship with the frequency of these plant-parasitic nematodes. Further studies, including molecular analysis and a vast number of samples, were recommended for accurate and specific identification of the species of the nematodes as well as utilizing multiple parameters to allow more statistical analysis about its morphometrics